Drones and responsibility : legal, philosophical and socio-technical perspectives on remotely controlled weapons /: legal, philosophical and socio-technical perspectives on remotely controlled weapons. (2016) - Di Nucci, Ezio; Santoni de Sio, Filippo
No abstract available